2004
DOI: 10.1677/joe.0.1810477
|View full text |Cite
|
Sign up to set email alerts
|

Role of leukemia inhibitor factor (LIF) in decidualisation of murine uterine stromal cells in vitro

Abstract: Decidualisation of uterine stromal cells is a prerequisite for implantation of the embryo in mice. Here we have used an in vitro culture system in which stromal cells decidualise as indicated by a number of markers, including an increase in alkaline phosphatase (ALP) activity. The latter was used as a quantitative marker of decidualisation in the presence of low (2%) fetal calf serum. Prostaglandin E(2) (PGE(2)), which is known to induce decidualisation, increased ALP activity, and this effect was blocked in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…Often, the genetic alteration prevents the survival of null mice to adulthood and thus studies on reproductive physiology are hampered, reviewed in Salamonsen et al (2001). Previous work has centred upon identifying possible targets of LIF during early pregnancy from comparisons between wild-type and Lif deficient mice (Fouladi-Nashta et al 2004, 2005, 2008, Sherwin et al 2004. However, this neither permits the study of the temporal and spatial influence of LIF, particularly during pregnancy nor does it address the possibility that the phenotype may partly arise from the gene deletion construct causing -cis or -trans effects on adjacent genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Often, the genetic alteration prevents the survival of null mice to adulthood and thus studies on reproductive physiology are hampered, reviewed in Salamonsen et al (2001). Previous work has centred upon identifying possible targets of LIF during early pregnancy from comparisons between wild-type and Lif deficient mice (Fouladi-Nashta et al 2004, 2005, 2008, Sherwin et al 2004. However, this neither permits the study of the temporal and spatial influence of LIF, particularly during pregnancy nor does it address the possibility that the phenotype may partly arise from the gene deletion construct causing -cis or -trans effects on adjacent genes.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments have shown that functional inactivation of LIFR by hLIF-05 is required for the arrest of murine rod differentiation in vitro (Neophytou et al 1997) and previous work in our laboratory has shown that LIF induced effects can be antagonised by hLIF-05 in cultured murine uterine stromal cells (Fouladi-Nashta et al 2004, 2008. However, this antagonist has not been used previously in vivo.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…It has been reported that LIF can enhance decidualization of endometrial stromal cells in humans (16). In vivo experiments showed that polyethylene glycol (PEG)-conjugated LIF antagonist treatment reduced the decidual area of implantation site (15).…”
Section: Lif-stat3-egr1 Signaling Pathway Plays a Critical Role In Dementioning
confidence: 99%
“…Conditional knock-out or transient suppression of STAT3 results in implantation failure, which suggests the critical role of STAT3 during implantation (11)(12)(13)(14). As a pleiotropic cytokine, LIF is also essential for mouse and human decidualization (15,16). However, the direct target gene of LIF-STAT3 pathway in mouse uterus during implantation remains poorly understood.…”
mentioning
confidence: 99%